Repetitive Construction Scheduling for Solo-Yogyakarta-NYIA Kulon Progo Toll Road Overpass using Line of Balance - Budiwirawan, Agung; Raharja, Edwin Firgyan; Arifin, Muhammad Faizal Ardhiansyah (Jurnal Teknik Sipil dan Perencanaan, 2023)
Repetitive construction requires continuous and uninterrupted supply of resources; hence, a suitable scheduling method that matches the work characteristics is required. Line of Balance is a scheduling method in the form of a line chart that represents recurring work. Considering the existing work items, Ngasem Overpass Bridge Solo-Yogyakarta-NYIA Kulon Progo Toll Road Project can be categorized as a repetitive construction project. Therefore, this research tries to apply LoB to this overpass project to determine whether LoB can efficiently manage a repetitive construction project. Two scheduling scenarios are applied in this study. The first scenario is implemented with the aim of producing a schedule that uses resources continuously and uninterruptedly. While the second scenario is applied to produce a schedule with the shortest duration. LoB based on the first scenario succeeded in compiling a schedule that uses resources continuously and uninterruptedly. Schedule based on the second scenario results in the shortest duration by severing the use of resources for short-duration jobs that are preceded and followed by longer-duration jobs. In addition to generating schedules according to the desired scenario, LoB has proved its ease in managing scheduling in terms of the continuity of resource use and the speed of completion of work.